Trial of Rivaroxaban in AntiPhospholipid Syndrome (TRAPS): Two‐year outcomes after the study closure. (29th November 2020) - Pengo, Vittorio; Hoxha, Ariela; Andreoli, Laura; Tincani, Angela; Silvestri, Elena; Prisco, Domenico; Fierro, Tiziana; Gresele, Paolo; Cafolla, Arturo; De Micheli, Valeria; Ghirarduzzi, Angelo; Tosetto, Alberto; et al.
Abstract: Background: Trial of Rivaroxaban in AntiPhospholipid Syndrome was a prospective randomized, open‐label, noninferiority study conducted in 14 centers in Italy. Rivaroxaban was compared with warfarin for the prevention of thromboembolic events, major bleeding, and vascular death in high‐risk, triple‐positive patients with antiphospholipid syndrome. Objective: The aim of this paper is to report the events during the 2‐year follow‐up after the study closure. Methods: On January 28, 2018, the trial was prematurely stopped by adjudication and safety committee for an excess of events in the rivaroxaban group. Randomized patients were advised on trial results and those randomized to rivaroxaban were solicited to switch to warfarin. All 14 participating centers were asked and accepted to follow their patients for clinical events. This report describes the rate of events that occurred between January 28, 2018, and January 28, 2020. Results: Of 120 randomized patients, 115 were available for follow‐up. Outcome events were two in six (33.3%) patients who remained on direct oral anticoagulants (DOACs) and six in 109 (5.7%) patients on warfarin (hazard ratio [HR] 6.9; 95% confidence interval [CI] 1.4‐34.5, P = .018). The two patients on DOACs (one taking dabigatran and one taking rivaroxaban) suffered from thromboembolic events, whereas of the six patients with composite outcomes on warfarin, three had thromboembolic events (HR for thrombosis 13.3; 95% CI 2.2‐79.9, P = .005). Conclusion: These data further support the use of warfarin in high‐risk patients with antiphospholipid syndrome.